Implementation of Discipline Character at Mts Muhammadiyah 1 Taman - Ani Nur Aisyah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this scientific work is to find out how to implement the character of the students' appearance in Mts Muhammadiyah 1 Taman during the pandemic. In the process of this study using the technique of taking data and observation. Based on the results of the study of the discipline character of the learners, it is very good to be exemplified. That is, with the Application tahfidz qur'an before the learning process begins and it must be followed by both students ranging from the seventh grade to Nine. Muhammadiyah education in Sambiroto Village during the covid-19 pandemic is conducted online or where the learning process is done from home through several applications, such as Zoom, Google meet, WhatsApp group, and others. In addition, the offline learning process is also carried out, but in accordance with health protocols. But even so, the learning process conducted at MTS Muhammadiyah 1 Taman in Sambiroto Village is still running smoothly until now.